2020
DOI: 10.1590/s2175-97902019000418124
|View full text |Cite
|
Sign up to set email alerts
|

Bioisosteric modification on melatonin: synthesis of new naphthalene derivatives, in vitro antioxidant activity and cytotoxicity studies

Abstract: Melatonin (MLT) is a strong free radical scavenger that protects the body from the deleterious effects of excess oxidants. Synthesis of MLT analogue compounds with antioxidant potency has recently attracted the interest of researchers. In general, the strategy consists of modifying the groups in the different sites of the indole ring or replacing the indole ring with an analogue. As part of our ongoing research, the antioxidant capacity and cytotoxicity of newly synthesized MLT analogue naphthalene derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…According to the study, these compounds were shown to be extremely potent antioxidant agents. The authors attribute the enhanced activity to the lack of the 6-methoxy group and the substitution of the indole ring with that of albocarbon [54].…”
Section: Spaczyska Et Al Developed and Synthesizedmentioning
confidence: 99%
“…According to the study, these compounds were shown to be extremely potent antioxidant agents. The authors attribute the enhanced activity to the lack of the 6-methoxy group and the substitution of the indole ring with that of albocarbon [54].…”
Section: Spaczyska Et Al Developed and Synthesizedmentioning
confidence: 99%
“… 7 , 8 In addition, the naphthamide derivatives showed a large spectrum of activities in various pharmacological fields like anticancer, 9 12 antibacterial, 13 15 antifungal, 15 17 anti-inflammatory, 18 and antioxidants. 19 Moreover, many important drugs used therapeutically in the research area contain naphthalene moieties such as nafcillin, bedaquiline, naproxen, tolnaftate, duloxetine, and propanolol ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalene is the simplest polycyclic aromatic hydrocarbon consisting of a fused pair of benzene rings. On the other hand, naphthamide derivatives containing a naphthalene nucleus are a common structural framework in various biologically active natural products, pharmaceuticals, and materials. , In addition, the naphthamide derivatives showed a large spectrum of activities in various pharmacological fields like anticancer, antibacterial, antifungal, anti-inflammatory, and antioxidants . Moreover, many important drugs used therapeutically in the research area contain naphthalene moieties such as nafcillin, bedaquiline, naproxen, tolnaftate, duloxetine, and propanolol (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…All of the tested compound in this study were synthesized and characterized on the basis of 1 H, 13 C NMR, mass spectra and elemental analysis. Thus, all data related on synthesis has been published (Shirinzadeh and Ghalia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%